(3Pjd Pjd GdCeGdjs - (3CHh Ydj GdbGdj , ESeGYjd Hf GdbGSe Hf YHOhf Hf gGQhf Hf YjSi Hf eMeO Hf SdeGf, CHh Ydj,J (B356 (3g` s ((3eMeO Hf EHQGgje Hf CMeO s)
(3ChdgG (B:s
(3BNQ GdRjGOI (B((3RjGOI(B) (3aj GdCeGdj GdeYQhaI HPjd GdPjd GdJj HJeGegG JeJ GdRjGOI CLeY JCdja CHj Ydj QMeg Gddg hfVQ hLgg s
(3BNQgG (B:s
(3Ydjc SdGe Gddg eG PQ TGb hZQO aj GdCjc GdMcGe GdeZQO Je GdLRA GdKGdK ef GdRjGOI aj GdCeGdj hHJeGeg Je LeY GdJCdja s
(3Vef eLehY , JQJjHgG (B: (3ef U (B168 (3L (B- (3U(B180 (3Cs
(3GfXQg eY GdCeGdjs
(3hojdGMX Cf GdYfhGf hVY bHd HOA GdcJGH HCQHY UaMGJs
(3hLGA Ydi GdUaMI GdCNjQI hgj HjVGA(B: (3GdfhGOQ dCHj Ydj ef GdCOHs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs